Atribut Ruang Sebagai Penanda Ruang Ritual Pada Pesarean Gunung Kawi Kabupaten Malang - Ayu, Dhinda; Antariksa, Antariksa; Ridjal, Abraham M. (RUAS, 2014)
Implementation of a ritual could not separate from its subject, time, space and things that used during the process. Space is a very important thing in the implementation of a ritual. Attribute or furniture inside the space that used to carry out the ritual activity also has a role to build a ritual space. Buildings that are considered sacral at Pesarean Gunung Kawi have space attribute which function to create a ritual space on the implementation of various types of rituals at that place. The purpose of this study is to determine the ritual space that formed by space attribute at Pesarean Gunung Kawi. The method used in this study is qualitative descriptive research. The result of this study showed that beside as a ritual space signage, space attribute also divide the space in accordance with the level of privacy.Keywords: attribute, space, ritual